Regarding physical assault of a worker of NS Construction by the worker of BUCG-ABC JV in the project site - Brac University (Brac University, 2023)
This record consists of general correspondence regarding physical assault of a worker of NS Construction by the worker of BUCG-ABC JV in BRACU new campus project site.